A tecno(contra)cultura do rock brasileiro em 1986 - Albuquerque, Ananda Zambi de (Universidade do Vale do Rio dos Sinos, 2023)
During the 1980s, Brazilian rock — or “BRock” — became a relevant spokesperson in favor of the end of the civil-military dictatorship. In addition to the musical sphere, the cultural universe of BRock was also linked to its visual dimension, once artists depended on inserts, posters, photos, videos, clothes and other materials to publicize their work and consolidate their identity. In this context, the video clip format became a landmark of BRock’s visuality of that period. This research intends to understand the audiovisual aspects of Brazilian rock in the 1980s, manifested specifically in video clips released in 1986, the most prosperous year of the BRock movement. Epistemologically, the research is part of a technocultural perspective, based on the concepts of Shaw (2008) and Fischer (2013), and adopts the Benjaminian cartography as methodological ballast for the incursions on the observed materials. The analyzes highlight the main characteristics of the audiovisualities of the video clips in question, presented in three constellations: urbanity, performance and reminiscence, in which remnants of updated countercultural traits in the audiovisual technoculture of the 1980s were identified. So, the research concludes that a certain techno(counter)culture that took shape in the national territory in the 1980s was decisive for dissatisfaction with the current political and social normative systems to be manifested through music, with the BRock movement – even if incorporated into show business – an important agent causing aesthetic ruptures and breakdowns in the media field, which contributed to shaping the identity of an era.
Keywords: Contracultura; Tecnocultura; Rock brasileiro; Videoclipe; Cartografia; Counterculture; Technoculture; Brazilian rock; Video clip; Cartography; ACCNPQ::Ciências Sociais Aplicadas::Comunicação